(untitled) (Bangladesh Journal of Botany, 2021)
NAC proteins are plant-specific transcription factors that have a variety of crucial roles in plant growth, development and response to stress. More than 100 members of NAC genes have been identified in maize genome, but almost all of them are not known for their expression profile and functions in plants. In this study, a NAC gene ZmNAC3 from maize was cloned using rapid amplification of cDNA ends. ZmNAC3 encodes a nucleus-targeted protein that has an extremely conserved NAC domain in the N-terminus. Expression of ZmNAC3 was greatly up-regulated by high salinity and low temperature, down-regulated by drought, but not responsive to exogenous abscisic acid (ABA). Furthermore, several cis-acting elements in response to stress were found in ZmNAC3 promoter region. These results suggest that ZmNAC3 encodes a NAC-domain protein which may function in the response of maize to abiotic stress.